Pure Blue and Highly Luminescent Quantum‐Dot Light‐Emitting Diodes with Enhanced Electron Injection and Exciton Confinement via Partially Oxidized Aluminum Cathode. Issue 11 (20th April 2017) - Cheng, Tai; Wang, Zhibin; Jin, Shengli; Wang, Fuzhi; Bai, Yiming; Feng, Haoxian; You, Baogui; Li, Yang; Hayat, Tasawar; Tan, Zhan'ao
Abstract : The balance injection of holes and electrons into a thin emissive quantum dot (QD) layer for efficient radiative recombination is critical to the color purity, stability, and efficiency of the QD‐based light‐emitting diodes (QD‐LEDs). Due to the difficulty of charge injection into wide band gap blue QD layer, the performance of blue QD‐LED is obviously inferior to the green and red counterparts. Here, high‐performance ZnCdS/ZnS graded core/shell‐based blue QD‐LEDs with partial oxidized aluminum cathode (Al:Al2 O3 ) via simple autoxidation are demonstrated. There is no any additional electron transport layer/hole transport layer involved in the device, which guarantees the color purity and simplifies the fabrication processes. Furthermore, the Al:Al2 O3 cathode greatly enhances the charge injection and exciton recombination, rendering significant improvement in luminance and current efficiency compared with the control devices with Al or Alq3/Al electrodes. A record luminance of over 13 000 cd m −2 has been achieved for blue QD‐LEDs with Al:Al2 O3 cathode. The findings of this study indicate that this simply processed and easily controlled autoxidation procedure is a promising strategy to achieve high‐performance blue QD‐LEDs. Abstract : A partially oxidized aluminum cathode (Al:Al2 O3 ) is applied in ZnCdS/ZnS quantum‐dot‐based blue light‐emitting diodes. Without any electron transport layer/hole transport layer involved, the Al:Al2 O3 cathode via simple autoxidation greatly enhances the electron injection and exciton radiative recombination, rendering a significant improvement in luminance (13 000 cd m −2 ) and current efficiency (1.1 cd A −1 ), while pure deep blue light emission is guaranteed.